6y+(-7)=3y-7+2y

Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.

3y-7+2y=6y-7

Add 3y and 2y.

5y-7=6y-7

Subtract 6y from both sides of the equation.

5y-7-6y=-7

Subtract 6y from 5y.

-y-7=-7

-y-7=-7

Add 7 to both sides of the equation.

-y=-7+7

Add -7 and 7.

-y=0

-y=0

Multiply each term in -y=0 by -1.

(-y)⋅-1=0⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=0⋅-1

Multiply y by 1.

y=0⋅-1

y=0⋅-1

Multiply 0 by -1.

y=0

y=0

Solve for y 6y+(-7)=3y-7+2y